Doubles, Twins and Triplets: Conning of Age in Contemporary Irish Drama - Bertha, Csilla (FOCUS: Papers in English Literary and Cultural Studies, 2000)
The abundance of doubles and split characters in contemporary Irish drama may be, in part, accounted for by the “double visions and double interpretations forced upon [the writers] by the facts of Irish history and of everyday life in Ireland” (Carpenter 178). Such characters embody the dualities, ambiguities, and insecurities in the Irish consciousness caused by centuries of colonial oppression, religious persecution, deprivation or mockery of cultural heritage, replacement of the mother tongue by the language of the colonisers, and other forms of humiliation. The uncertainty of identity was enhanced by the colonial stereotypes the English invented for the Irish and persuaded them to accept: “an identity was proposed for the natives, which cast them as foils to the occupiers” (Kiberd 9). It thus became impossible for the Irish to maintain an independent notion of identity and instead they came to see themselves always in comparison or contrast with the English. Similarly, the whole “Ireland... is never to be seen in itself, but as a flawed version of England” (Seathrún Céitinn qtd. in Kiberd 14).